Pengaruh Citra Merek dan Kualitas Produk terhadap Minat Beli Produk Skincare Skintific pada Perempuan di Kota Yogyakarta - Cindy Apriliani; Yulita Muhidin; Kristiana Sri Utami (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of brand image and product quality on the interest in buying Skintific skincare products in women in Yogyakarta City. The method in this study uses a quantitative approach with a purposive sampling technique involving 75 respondents who have previously used Skintific skincare products. Data were obtained through questionnaires and processed using multiple linear regression analysis using SPSS 25. The results of this study show that both brand image and product quality have results that do not affect either partially or simultaneously buying interest. These findings provide practical advice for marketers to strengthen brand image and maintain product quality to increase consumer purchase interest.